Association Between the Use of Sodium Bicarbonate and Mortality in Acute Kidney Injury Using Marginal Structural Cox Model. Issue 10 (October 2019) - Zhang, Zhongheng; Mo, Lei; Ho, Kwok M.; Hong, Yucai
Abstract : Objective: Acute kidney injury with metabolic acidosis is common in critically ill patients. This study assessed the associations between the use of IV sodium bicarbonate and mortality of patients with acute kidney injury and acidosis. Design: The study was conducted by using data from Beth Israel Deaconess Medical Center, which included several ICUs such as coronary care unit, cardiac surgery recovery unit, medical ICU, surgical ICU, and trauma-neuro ICU. Marginal structural Cox model was used to assess the relationship between receipt of sodium bicarbonate and hospital mortality, allowing pH, PaCO2, creatinine, and bicarbonate concentration as time-varying predictors of sodium bicarbonate exposure while adjusting for baseline characteristics of age, gender, Sequential Organ Failure Assessment score, acute kidney injury stage, Elixhauser score, quick Sequential Organ Failure Assessment, and Simplified Acute Physiology Score II. Setting: A large U.S.-based critical care database named Medical Information Mart for Intensive Care. Patients: Patients with Kidney Disease: Improving Global Outcomes acute kidney injury stage greater than or equal to 1 (> 1.5 baseline creatinine) and one measurement of acidosis (pH ⩽ 7.2). Baseline creatinine was estimated using the Chronic Kidney Disease Epidemiology Collaboration equation. Interventions: None. Measurements and Main Results: Of the 3, 406 eligible patients, 836 (24.5%) had received sodium bicarbonate treatment. Patients who received sodium bicarbonate treatment had a higher Sequential Organ Failure Assessment (9 vs 7; p < 0.001), lower pH (7.16 vs 7.18; p < 0.001), and bicarbonate concentration (16.51 ± 7.04 vs 20.57 ± 6.29 mmol/L; p < 0.001) compared with those who did not receive sodium bicarbonate. In the marginal structural Cox model by weighing observations with inverse probability of receiving sodium bicarbonate, sodium bicarbonate treatment was not associated with mortality in the overall population (hazard ratio, 1.16; 95% CI, 0.98–1.42; p = 0.132), but it appeared to be beneficial in subgroups of pancreatitis (hazard ratio, 0.53; 95% CI, 0.28–0.98; p = 0.044) and severe acidosis (pH < 7.15; hazard ratio, 0.75; 95% CI, 0.58–0.96; p = 0.024). Furthermore, sodium bicarbonate appeared to be beneficial in patients with severe bicarbonate deficit (< –50 kg·mmol/L). Conclusions: In the analysis by adjusting for potential confounders, there is no evidence that IV sodium bicarbonate is beneficial for patients with acute kidney injury and acidosis. Although the study suggested potential beneficial effects in some highly selected subgroups, the results need to be validated in experimental trials. Abstract : Supplemental Digital Content is available in the text.